Inequities of global mobility: socioeconomic stratification in the meanings of a university education for international students. Issue 1 (2nd January 2021) - Glass, Chris R.; Streitwieser, Bernhard; Gopal, Anita
ABSTRACT: This study explores socioeconomic stratification in the experiences and relationships that international students identify as meaningful during their university education. Researchers used interview data from 40 international students to explore the role of funding in the qualities of their academic experiences and the support networks they accessed during their university studies. The authors describe how well-financed, single-resourced students took a more cosmopolitan, intrinsic approach to engagement in the formal and informal curriculum, whereas students who pooled funding from many sources described a more career-minded, utilitarian approach. They discuss how the underlying challenges faced by international students are localised reflections of global processes of socioeconomic stratification and inequality among individuals. They discuss the benefits of greater cross-border mobility and interconnectedness for international students from varied socioeconomic backgrounds, but also how the distribution of benefits remain chronically and unevenly distributed.